Goal-Directed vs Traditional Approach to Intraoperative Fluid Therapy during Open Major Bowel Surgery: Is There a Difference? - Prabhu P. Sujatha; Anitha Nileshwar; H. M. Krishna; S. S. Prasad; Manjunath Prabhu; Shobha U. Kamath (Anesthesiology Research and Practice)
Introduction. Optimum perioperative fluid therapy is important to improve the outcome of the surgical patient. This study prospectively compared goal-directed intraoperative fluid therapy with traditional fluid therapy in general surgical patients undergoing open major bowel surgery. Methodology. Patients between 20 and 70 years of age, either gender, ASA I and II, and scheduled for elective open major bowel surgery were included in the study. Patients who underwent laparoscopic and other surgeries were excluded. After routine induction of general anaesthesia, the patients were randomised to either the control group (traditional fluid therapy), the FloTrac group (based on stroke volume variation), or the PVI group (based on pleth variability index). Fluid input and output, recovery characteristics, and complications were noted. Results. 306 patients, with 102 in each group, were enrolled. Five patients (control (1), FloTrac (2), and PVI (2)) were inoperable and were excluded. Demographic data, ASA PS, anaesthetic technique, duration of surgery, and surgical procedures were comparable. The control group received significantly more crystalloids (3200 ml) than the FloTrac (2000 ml) and PVI groups (1875 ml), whereas infusion of colloids was higher in the FloTrac (400–700 ml) and PVI (200–500 ml) groups than in the control group (0–500 ml). The control group had significantly positive net fluid balance intraoperatively (2500 ml, 9 ml/kg/h) compared to the FloTrac (1515 ml, 5.4 ml/kg/h) and PVI (1420 ml, 6 ml/kg/h) groups. Days to ICU stay, HDU stay, return of bowel movement, oral intake, morbidity, duration of hospital stay, and survival rate were comparable. The total number of complications was not different between the three groups. Anastomotic leaks occurred more often in the Control group than in the others, but the numbers were small. Conclusions. Use of goal-directed fluid management, either with FloTrac or pleth variability index results in a lower volume infusion and lower net fluid balance. However, the complication rate is similar to that of traditional fluid therapy. This trial is registered with CTRI/2018/04/013016.